Sustainable Development Revisited: Rethinking Growth-Centric Paradigms Through the Lens of the Sabbath - Graham, Molly (European Journal of Sustainable Development, 2024)
This paper argues that the current growth-centric paradigm of sustainable development is fundamentally flawed and proposes a paradigm shift towards the biblical concept of the Sabbath. It critiques the internal contradictions of the SDGs and challenges the unsustainable pursuit of infinite growth in addressing social and ecological crises. By exploring Sabbath’s principles of rest, recalibration, and redistribution, the paper offers an ethical foundation for self-limitation and a basis for human identity beyond productivity